The relationship between smoking status and salivary flow rate in inhaled general anesthesia patients at Brebes Regional Hospital - Nabitha, Kanaya; Suandika, Made; Susanto, Amin; Novitasari, Dwi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background :Smoking is one of the habits that is inherent in humans because it is addictive. Active smokers in Indonesia have increased significantly in 10 years. Smoking has a negative impact on health, one of which is changes in salivary flow rate. Changes in salivary flow rate in smokers can cause complications in the airway when performing surgery using inhalation general anaesthesia. The purpose of this study was to determine the relationship between smoking status and salivary flow rate in patients with inhalation general anaesthesia. Method : This type of research is observational analytic with a cross sectional approach. The sample in the study was 35 respondents with 4 inclusion criteria. The sample in this study was taken with purporsive sampling technique. Data collection stimulated saliva by suction method. Data analysis using univariate and bivariate analysis, namely the Chi-Square test. Results : The results showed that inhalation general anaesthesia patients were more smokers with 24 respondents (68.6%) and respondents who experienced changes in salivary flow rate obtained the most respondents who experienced hypersaliva as many as 15 respondents (42.9%). The results of bivariate analysis using the Chi-Square test showed that 11 respondents (31.4%) who smoked experienced hypersaliva with a p-value of 0.000 <0.05. Conclusion : There is a relationship between smoking status and salivary flow rate in inhalation anaesthesia patients, namely the increase in salivary flow rate in smoking respondents with inhalation general anaesthesia.